Chapter An Italian Hero for China. Reading Marco Polo in the Fascist Era - DE GIORGI, Laura (Connessioni. Studies in Transcultural History, 2022)
This article offers an overview of the readings of Marco Polo's ventures offered to the Italian public opinion during the Fascist era. Marco Polo's image was adapted to the needs of patriotic pedagogy, propaganda of Fascist values and colonial aspirations, and the attempt to redefine Rome's political, economic and cultural role in the world. In a complex mix of academic and popular readings, the official discourse transformed the Venetian traveller into a symbol of Italianness in China in order to legitimize Fascist Italy's ambitions and expectations and stress its distinct identity in comparison with the other western powers. Although Chinese reception of this discourse was limited by several factors at that time, this process certainly helped establish Marco Polo's iconic significance in Sino-Italian cultural diplomacy well into the twentieth century.